Revisiting Existed Syllabus in Poetry Class: An Interactive Approach - Deta Maria Sri Darta; Ervin Suryaningsih; Rindang Widiningrum (Universitas PGRI Semarang, 2023)
Poetry has become less and less preferred by the students. Poetry has been viewed as a boring subject. This is because the process of learning and teaching poetry is considered as a routine activity. This article seeks ways to make poetry become an interesting subject to learn by examining the existing poetry syllabus and proposing a more interactive syllabus. Ethnography was used in this study to gather the information. Lecturers and students will have to work together and collaborate in conducting a conducive atmosphere to reduce the anxiety in learning and teaching poetry. By reducing the anxiety, students will find that learning poetry will give them something more than just analyzing poems. Learning poems will contribute to their English development. The result of this study is a proposed syllabus that is more interactive compared to the existing one, especially the class activities; that are employing collage and mirror writing as ways to appreciate poems read. The implication of the proposed syllabus is that this syllabus should be implemented to see how far the proposed syllabus helps to reduce learning anxiety and make the learning process of poetry class become more interactive.